Producción de una serie radiofónica educativa sobre salud sexual y reproductiva para adolescentes de la red de niños, niñas y adolescentes comunicadores de Pichincha Corape – Plan. - Ayala Sánchez, Carla Daniela (2013)
The reality in Ecuador reveals an increase in the rate of teenage pregnancies as a result of having sex irresponsibly, exposing addition to contracting any sexually transmitted infection and some affect themselves emotionally from this current problem arises idea to study some of the factors that trigger this problem, and thus provide possible solutions from communication. Communication is established as the tool to connect the problems that arise with possible solutions, creating participatory spaces where teens work on the issue of sexual and reproductive health. This paper presents a proposal for educational radio sexual and reproductive health, which is a dramatized series of 3 episodes, which proposes a participatory space for teenagers between 14 and 18 years old, that worked with network of children and teenagers Pichincha communicators CORAPE - PLAN where more than learn and participate in the topic, they can exercise radio communication as a means of expression and integration for input is problematic.